You are not alone - Hendricks, Greer; Pekkanen, Sarah (New York : St. Martin's Press, 2020)
Shay Miller has three strikes against her: no job, no apartment, no love in her life. But when she witnesses a perfectly normal looking young woman about her age make the chilling decision to leap in front of an ongoing subway train, Shay realizes she could end up in the same spiral. She is intrigued by a group of women who seem to have it all together, and they invite her with the promise: "You are not alone." Why not align herself with the glamorous and seductive Moore sisters, Cassandra and Jane? They seem to have beaten back their demons, and made a life on their own terms-a life most people can only ever envy. They are everything Shay aspires to be, and they seem to have the keys to getting exactly what they want.
Keywords: Female friendship -- Fiction; Young women -- Fiction; Secrecy -- Fiction; Jealousy -- Fiction; New York (N.Y.) -- Fiction; Psychological fiction; Thrillers (Fiction)